Surface and destroy : the submarine gun war in the Pacific - Sturma, Michael, 1950- (University Press of Kentucky, 2011)
World War II submariners rarely experienced anything as exhilarating or horrifying as the surface gun attack. Between the ocean floor and the rolling whitecaps above, submarines patrolled a dark abyss in a fusion of silence, shadows, and steel, firing around eleven thousand torpedoes, sinking Japanese men-of-war and more than one thousand merchant ships. But the anonymity and simplicity of the stealthy torpedo attack hid the savagery of warfare-a stark difference from the brutality of the surface gun maneuver. As the submarine shot through the surface of the water, confined sailors scrambled t.